On‐Water NiFe2O4 Nanoparticle‐Catalyzed One‐Pot Synthesis of Biofunctionalized Pyrimidine‐Thiazole Derivatives: In Silico Binding Affinity and In Vitro Anticancer Activity Studies. Issue 39 (24th October 2018) - Sharma, Archi; Gudala, Satish; Ambati, Srinivasa Rao; Mahapatra, S. P.; Raza, Asif; L., Aruna; Payra, Soumen; Jha, Anubhuti; Kumar, Awanish; Penta, Santhosh; Banerjee, Subhash
Abstract: A series of novel integrated bio‐active pyrimidine‐thiazole derivatives have been efficiently synthesized via NiFe2 O4 ‐NP‐catalyzed, one‐pot three component reactions in aqueous ethanol as green solvent. The synthesized compounds were screened against different cancer cell lines (A375, HeLa, and MCF‐7) and it was observed that thiazole derivatives exhibited good anticancer activity against A375 and MCF‐7 cancer cell line comparable to erlotinib. Compound 4 h displayed comparable anticancer activity against all the three cancer cell lines A375, HeLa and MCF‐7. The in silico molecular docking studies for all the newly synthesized compounds were shown good to excellent binding affinity for Hsp90 proteins. In ADME analysis, the best result for absorption and metabolism is shown by the compound 4e. While the excretory parameter is found to be the best for compound 4 h. Abstract : A NiFe2 O4 ‐NP‐catalyzed, one‐pot, green, efficient synthetic method has been described for biofunctionalized pyrimidine‐thiazole derivatives. All the novel synthesized derivatives were exhibited good anticancer activity against different cancer cell lines A375, HeLa, and MCF‐7.The in silico molecular docking studies for all the derivatives were shown good to excellent binding affinity towards Hsp90 proteins. Moreover, various pharmacokinetic parameters were also estimated for ADME analysis.